KATA SAPAAN KEKERABATAN BAHASA MELAYU JAMBI DI DESA TERITI KECAMATAN SUMAY KABUPATEN TEBO - Sabar Saputra; Sainil Amral (Universitas Batanghari, 2020)
This research aims at describing the shape and the use of greetings in Jambi Malay language kinship in Desa Teriti Kecamatan Sumay Kabupaten Tebo. By doing this research, it is expected that the greetings in Desa Teriti Kecamatan Sumay Kabupaten Tebo can be continuously preserced by the speakers. This research uses qualitative descriptive method. Qualitative descriptive method is used in conducting data and explaining it scientifically. The source of the research data is native speaker of Jambi Malay in Desa Teriti Kecamatan Sumay Kabupaten Tebo. In collecting the data, observation, well-organized interview, and record technique are used. From the result of the research, it can be concluded that there is a direct and indirect of greetings in Jambi Malay language kinship in Desa Teriti Kecamatan Sumay Kabupaten Tebo. The direct kinship which is related with blood line consists of 2 types in sequence starts from piyut, gedeh, kopet, datok, nyai, bak, mak, kolop, supek, piyut dan icit-icit-icit and secara tak berurutan yang terdiri dari abang wo, bah, adek, wo, mewo, pak ngah, mengah, busu, mesu, abang, mbok, nak, kolop, supek. Meanwhile the indirect kinship which is related to marriage line are abang, mak + nama anak tertua, nama diri, bak, mek, abang, mbok, nama diri, abang, mak + nama menantu. There are two functions of greetings in Jambi Malay language kinship in Desa Teriti Kecamatan Sumay Kabupaten Tebo, they are: to mark on other speakers and to defend social relationship between the speakers. The greetings in the beginning of the sentence is to mark on other speakers, while the greeting at the end of the sentence is to defent social relationship between speakers.